A metal oxide-activated carbon composite material and its preparation method and application

By synchronously preparing metal oxides and activated carbon, the molecular level fusion of the two was achieved, and uniformity and defect problems in the preparation of existing composite materials were solved, and supercapacitor electrode materials with high specific capacitance and good cycle stability were obtained.

CN116072443BActive Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202111276743.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-30
Publication Date
2025-05-02
Estimated Expiration
2041-10-30

AI Technical Summary

Technical Problem

In the existing carbon material/metal oxide composite preparation technology, the preparation process of carbon material and metal oxide is independent, resulting in poor uniformity of composite materials and many structural defects, making it difficult to achieve high quality and excellent electrochemical properties.

Method used

By synchronizing the preparation process of metal oxides with the preparation process of activated carbon, using petroleum coke-based activated carbon as a skeleton support, nanometal oxide particles are introduced simultaneously in situ to achieve molecular-level fusion of the two materials.

Benefits of technology

The prepared metal oxide-activated carbon composite material has high specific capacitance, good rate performance and cycle stability, and is suitable for electrode materials of supercapacitors.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a metal oxide-activated carbon composite material and a preparation method and application thereof, wherein the composite material comprises a first metal oxide, a metal-promoting oxide and activated carbon. The preparation method comprises preparing a dry glue containing a first metal-promoting metal and oxidized petroleum coke respectively; then mixing the dry glue containing a first metal-promoting metal, the oxidized petroleum coke and an activator under an inert atmosphere for heat treatment; and treating the material obtained by the heat treatment under an oxidizing atmosphere to obtain a metal oxide-activated carbon composite material. A working electrode using the above composite material and a preparation method thereof are also provided. The metal oxide-activated carbon composite material of the present invention uses metal oxide to ensure the specific capacitance value of the composite material, and through the skeleton support of the carbon material, the structural collapse of the metal oxide during the charge and discharge process is well alleviated to ensure the transfer of electrons.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials, and in particular relates to an activated carbon-containing composite material and a preparation method thereof. Background Art

[0002] Among the many energy conversion and storage technologies, supercapacitors combine the excellent properties of traditional capacitors and secondary batteries, with the advantages of high power density, multiple charge and discharge cycles, long service life, and more significant high and low temperature characteristics. They have very broad market development prospects in the fields of wind energy, photovoltaic power generation, new energy vehicles, national defense, aerospace, electronic communications, etc.

[0003] Electrolyte, diaphragm and electrode materials are the three basic components of supercapacitors. The three together determine the comprehensive performance of supercapacitors, among which electrode materials are the most critical. Electrode materials include double-layer electrode materials and pseudocapacitor electrode materials. Pseudocapacitor electrode materials have high capacitance values. Under the condition of the same specific surface area, the specific capacitance value is about 10 to 100 times that of double-layer electrode materials. Common ones are metal oxides, among which MnO2 has low cost, low pollution, wide voltage window, and theoretical specific capacitance value reaches 1380 F / g. However, when used as electrode materials, metal oxides often have poor conductivity and high resistivity, resulting in large capacitance loss at high current density. Problems such as volume expansion effect and active material particle rupture seriously affect the long-term stability of the electrode. Carbon materials are the most common double-layer electrode materials, among which activated carbon is the earliest carbon electrode material used in supercapacitors and is also the most studied electrode material at present. As a supercapacitor electrode material, the attraction of activated carbon lies in its good conductivity, ultra-high specific surface area, and adjustable void structure. In addition, activated carbon has the advantages of abundant raw materials, low price, good processing performance and stable chemical properties. Activated carbon has become the electrode material for supercapacitors with the most industrial prospects.

[0004] When the same type of electrode material is used alone, there will always be certain performance limitations, and it cannot fully meet the performance requirements of supercapacitors in all aspects. Using carbon materials and metal oxides as electrode materials has become a new technical development trend.

[0005] At present, the preparation process of composite materials of carbon materials and manganese dioxide mostly uses expensive carbon nanotubes and graphene as carbon precursors. Patent CN 108217733 A uses graphite as raw material, intercalates and expands graphite through intercalation agents, oxidants, and expanders to obtain graphene-like expanded graphite, and then reacts with potassium permanganate to grow manganese dioxide on carbon nanosheets to obtain carbon-manganese dioxide composite materials. Patent CN 109637839A discloses a carbon nanotube / manganese dioxide composite electrode material, which uses carbon cloth treated with nitric acid to load carbon nanotubes, and then uses potassium permanganate and manganese sulfate as manganese sources for hydrothermal synthesis to prepare composite electrode materials. Patent CN 105826088 A uses potassium permanganate as a precursor to in-situ redox-grow manganese dioxide nanosheets on the surface of a carbon aerogel with a three-dimensional network structure composed of one-dimensional carbon nanofibers and two-dimensional flaky carbon to obtain a carbon aerogel / manganese dioxide composite electrode material. The high specific surface area and porosity of the carbon aerogel improve the defects of poor conductivity and small specific surface area of ​​manganese dioxide, so that the composite material has more chemical reaction sites and electrolyte conduction paths, and the electrochemical performance is greatly improved. However, the preparation process of carbon aerogel using polyacrylonitrile as raw material is very complicated. Patent CN 105405680A uses manganese sulfate and potassium permanganate as manganese sources to prepare manganese dioxide nanosheets through hydrothermal synthesis, and then uses methane as a carbon source and adopts a chemical vapor deposition method to perform carburization to prepare a carbon particle / manganese dioxide composite electrode material to solve the problems of high internal resistance and poor charge and discharge stability of manganese dioxide. Summary of the invention

[0006] During the research process, the applicant found that the current carbon material / metal oxide composite material preparation technology mostly uses carbon precursors with good conductivity such as graphene, carbon nanotubes, and carbon aerogels, and improves the performance of the composite material by improving the preparation method and structural properties of the carbon precursor. However, the preparation of carbon materials and metal oxides are two independent processes. Whether it is first synthesizing the carbon material and then synthesizing the metal oxide through hydrothermal methods, or first synthesizing a certain crystal form of metal oxide and then carburizing it, the composite material prepared in this way has relatively poor uniformity and more structural defects. Therefore, it is of great significance to develop metal oxide-carbon composite materials with higher quality and better electrochemical properties.

[0007] In view of the problems existing in the prior art, the main purpose of the present invention is to provide a metal oxide-activated carbon composite material and a preparation method and application thereof, the preparation process of the metal oxide is carried out simultaneously with the preparation process of the activated carbon, the fusion of the two materials at the molecular level is achieved, nano-metal oxide particles are simultaneously introduced in situ during the formation of the activated carbon pore structure, the advantages of the two materials are fully integrated and exerted, and the prepared composite material, when used as a supercapacitor electrode material, has the advantages of high specific capacitance, good rate performance and good cycle stability.

[0008] In order to achieve the above object, the technical solution of the present invention is as follows:

[0009] 1. The present invention provides a metal oxide-activated carbon composite material, which includes a first metal oxide, a co-metal oxide and activated carbon. Based on the weight of the composite material, the content of the first metal oxide is 4 to 60%, preferably 5 to 50%; the content of the co-metal oxide is 0.9 to 40%, preferably 1 to 30%; and the content of activated carbon is 20 to 95%, preferably 20 to 90%.

[0010] Furthermore, in the above-mentioned metal oxide-activated carbon composite material, the activated carbon is petroleum coke-based activated carbon.

[0011] Furthermore, in the above-mentioned metal oxide-activated carbon composite material, the first metal is selected from one or more of the metals of Group VIIB and Group VIII, and specifically can be one or more of manganese, nickel, and cobalt, preferably manganese.

[0012] Furthermore, in the above-mentioned metal oxide-activated carbon composite material, the auxiliary metal is at least one of the lanthanide elements, preferably lanthanum and / or cerium.

[0013] Furthermore, the metal oxide-activated carbon composite material has a specific surface area of ​​300 to 2500 m 2 / g; preferably 500 to 1600 m 2 / g.

[0014] Furthermore, the defect degree of the above metal oxide-activated carbon composite material is 0.8 to 2.0, preferably 0.9 to 1.7. The defect degree refers to the defect degree of the composite material at the wave number of 1590 cm in Raman analysis. -1 The absorption peak and wave number are at 1340 cm -1 The ratio of the peak intensities of the absorption peaks.

[0015] 2. The present invention provides a method for preparing a metal oxide-activated carbon composite material, which specifically comprises the following steps:

[0016] (1) preparing a dry glue containing a first metal and a co-metal;

[0017] (2) oxidizing the petroleum coke to obtain oxidized petroleum coke;

[0018] (3) mixing the dry glue containing the first metal-co-metal obtained in step (1), the oxidized petroleum coke obtained in step (2) and an activator, mixing them evenly and then heat treating them in an inert atmosphere;

[0019] (4) The material obtained by the heat treatment in step (3) is treated in an oxidizing atmosphere, and the obtained solid product is further washed and dried to obtain a metal oxide-activated carbon composite material.

[0020] In the preparation method of the above-mentioned metal oxide-activated carbon composite material, the preparation of the dry gel containing the first metal-co-metal in step (1) is carried out by a sol-gel method, and the specific process is as follows: the first metal precursor, the co-metal precursor and the complexing agent are dissolved in a solvent, heated to a sol state, and then dried to obtain the dry gel containing the first metal-co-metal.

[0021] In the preparation method of the above metal oxide-activated carbon composite material, the first metal is selected from one or more of Group VIIB and Group VIII metals, specifically one or more of manganese, nickel, and cobalt, preferably manganese.

[0022] In the preparation method of the above metal oxide-activated carbon composite material, the first metal precursor is a salt containing the first metal, which can be an inorganic salt and / or an organic salt, specifically one or more of nitrate, sulfate, acetate, and chloride.

[0023] In the preparation method of the above-mentioned metal oxide-activated carbon composite material, the first metal precursor is one or more of manganese nitrate, manganese chloride, manganese sulfate, manganese acetate, nickel nitrate, nickel chloride, nickel acetate, nickel sulfate, cobalt nitrate, cobalt chloride, cobalt acetate, and cobalt sulfate.

[0024] In the above-mentioned method for preparing the metal oxide-activated carbon composite material, the auxiliary metal is at least one of the lanthanide elements, preferably lanthanum and / or cerium;

[0025] In the preparation method of the above metal oxide-activated carbon composite material, the metal precursor may be a salt containing a metal, and may be an inorganic salt and / or an organic salt, specifically one or more of nitrate, sulfate, acetate and chloride.

[0026] In the preparation method of the above metal oxide-activated carbon composite material, the co-metal precursor can be one or more of cerium nitrate, cerium sulfate, cerium chloride, cerium acetate, lanthanum chloride, lanthanum nitrate, lanthanum sulfate, and lanthanum acetate.

[0027] In the preparation method of the above metal oxide-activated carbon composite material, the complexing agent is one or more of citric acid, maleic acid, oxalic acid, ammonium oxalate, ethanolamine, diethanolamine, triethanolamine, polyvinyl pyrrolidone, glucose, and tartaric acid.

[0028] In the preparation method of the above metal oxide-activated carbon composite material, the solvent is one or more of water and low molecular alcohol solvents, specifically one or more of water, ethanol, methanol, isopropanol, and n-butanol.

[0029] In the method for preparing the above metal oxide-activated carbon composite material, the mass ratio of the first metal precursor to the co-metal precursor is 10:1 to 1:1, preferably 8:1 to 2:1.

[0030] In the method for preparing the above metal oxide-activated carbon composite material, the mass ratio of the first metal precursor to the complexing agent is 3:1 to 1:2, preferably 2:1 to 1:2.

[0031] In the method for preparing the metal oxide-activated carbon composite material, the temperature of the heating treatment is 35 to 70°C.

[0032] In the preparation method of the above metal oxide-activated carbon composite material, after the first metal precursor, the auxiliary metal precursor and the complexing agent are dissolved in a solvent, the pH of the system is preferably adjusted to 5.5-7.5, for example, by using ammonia water with a concentration of 15wt%-30wt%.

[0033] In the preparation method of the above metal oxide-activated carbon composite material, drying can be carried out by air drying and vacuum drying, preferably vacuum drying, the drying temperature is 60-120°C, preferably 80-100°C, and the drying time is 2-24h, preferably 5-12h.

[0034] In the above-mentioned method for preparing the metal oxide-activated carbon composite material, the petroleum coke in step (2) is a solid product produced by a delayed coking device, and the particle size of the petroleum coke raw material is 10 to 500 μm, preferably 30 to 300 μm. Furthermore, the petroleum coke preferably has a volatile matter content between 5wt% and 20wt%.

[0035] In the preparation method of the metal oxide-activated carbon composite material, the specific process of oxidizing the petroleum coke in step (2) is as follows: the petroleum coke is ground and pulverized, mixed with an oxidant solution, and then washed and dried to obtain oxidized petroleum coke. The oxidant is one or more of nitric acid, hydrogen peroxide, potassium permanganate, and potassium perchlorate. The concentration of the oxidant is 2 to 10 mol / L, preferably 3 to 8 mol / L.

[0036] In the preparation method of the above-mentioned metal oxide-activated carbon composite material, the activator in step (3) is one or more of sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, potassium bicarbonate, sodium bicarbonate, calcium hydroxide, and magnesium hydroxide, preferably one or more of sodium hydroxide, potassium hydroxide, and potassium carbonate.

[0037] In the preparation method of the above-mentioned metal oxide-activated carbon composite material, in step (3), the dry glue containing the first metal-promoter metal obtained in step (1), the oxidized petroleum coke obtained in step (2) and the activator are mixed and heat-treated, which helps to further disperse the generated metal species and the promoter species (cerium species / lanthanum species) and improve the dispersion degree of the metal species and the promoter species.

[0038] In the preparation method of the metal oxide-activated carbon composite material, the mass ratio of the petroleum coke raw material to the activator is 1:0.2 to 1:10, preferably 1:0.5 to 1:5. The mass ratio of the first metal precursor to the petroleum coke raw material is 4:1 to 0.05:1, preferably 3:1 to 0.1:1.

[0039] In the above-mentioned method for preparing the metal oxide-activated carbon composite material, before the heat treatment in step (3), the gas in the device is fully replaced with an inert atmosphere, and the inert atmosphere is one or more of nitrogen, helium, neon, and argon, preferably nitrogen and / or helium.

[0040] In the above-mentioned method for preparing the metal oxide-activated carbon composite material, the heat treatment temperature in step (3) is 700-1000° C., preferably 700-900° C.; the heat treatment time is 20-120 min, preferably 20-100 min.

[0041] In the preparation method of the metal oxide-activated carbon composite material, during the heat treatment process of step (3), the thermal decomposition process of the first metal precursor, the auxiliary metal precursor, and the complexing agent is carried out simultaneously with the activation and pore-forming process of the petroleum coke. During the process of the activator gradually forming and expanding the pores of the petroleum coke, the first metal precursor and the auxiliary metal precursor thermally decomposed to generate the first metal oxide and the auxiliary metal oxide (such as cerium oxide or lanthanum oxide) participate in the reaction at the same time, and gradually disperse and deposit into the pores as the pore-forming process proceeds. During the activation process of the petroleum coke, metal oxides with different valence states are generated in situ in the system, and there may also be a certain amount of metal elements. As the pores of the petroleum coke become rich and developed, these metal oxides are evenly distributed on the inner and outer surfaces of the petroleum coke.

[0042] In the above-mentioned method for preparing the metal oxide-activated carbon composite material, the oxidation treatment temperature in step (4) is 20 to 200° C., preferably 20 to 150° C.; the oxidation treatment time is 20 to 240 min, preferably 30 to 180 min.

[0043] In the above-mentioned method for preparing the metal oxide-activated carbon composite material, the oxidizing atmosphere in step (4) is one or more of air, oxygen, and an oxygen-carrier gas mixture, preferably at least one of air and an oxygen-carrier gas mixture; the carrier gas in the oxygen-carrier gas mixture is at least one of nitrogen and an inert gas, and further, the volume concentration of oxygen in the oxygen-carrier gas mixture is 2 to 30%, preferably 5 to 25%.

[0044] In the preparation method of the metal oxide-activated carbon composite material, after the activation process of the petroleum coke in step (4) is completed, the valence state of the metal species on the surface of the activated carbon can be flexibly adjusted by an oxidation post-treatment method. In an oxidizing atmosphere, the auxiliary metal oxide (such as cerium oxide and / or lanthanum oxide) realizes the storage and release of oxygen through the mutual conversion of valence states, and quickly converts O2 in the oxidizing atmosphere into active oxygen. The concentration of active oxygen species is increased by the generation and migration of oxygen vacancies, and the active oxygen species are accurately transferred to the first metal of different valence states, so as to selectively realize the low-temperature oxidation of the first metal and adjust the amount of nano-first metal oxide on the surface of the activated carbon.

[0045] In the preparation method of the above metal oxide-activated carbon composite material, the water washing in step (4) is washing with deionized water, distilled water or ultrapure water, and the mass ratio of water to solid phase material during water washing is 10:1 to 50:1, preferably 10:1 to 30:1.

[0046] In the above-mentioned method for preparing the metal oxide-activated carbon composite material, the drying temperature in step (4) is 20 to 120° C., preferably 40 to 105° C.; the drying time is 1 to 24 hours, preferably 4 to 12 hours.

[0047] 3. The present invention provides a metal oxide-activated carbon composite material obtained by the above-mentioned preparation method, wherein the composite material includes a first metal oxide, a co-metal oxide and activated carbon. Based on the weight of the composite material, the content of the first metal oxide is 4 to 60%, preferably 5 to 50%; the content of the co-metal oxide is 0.9 to 40%, preferably 1 to 30%; and the content of activated carbon is 20 to 95%, preferably 20 to 90%.

[0048] Furthermore, in the above-mentioned metal oxide-activated carbon composite material, the activated carbon is petroleum coke-based activated carbon.

[0049] Furthermore, in the above-mentioned metal oxide-activated carbon composite material, the first metal is selected from one or more of the metals of Group VIIB and Group VIII, and specifically can be one or more of manganese, nickel, and cobalt, preferably manganese.

[0050] Furthermore, in the above-mentioned metal oxide-activated carbon composite material, the auxiliary metal is at least one of the lanthanide elements, preferably lanthanum and / or cerium.

[0051] Furthermore, the metal oxide-activated carbon composite material has a specific surface area of ​​300 to 2500 m 2 / g; preferably 500 to 1600 m 2 / g.

[0052] Furthermore, the defect degree of the above-mentioned metal oxide-activated carbon composite material is 0.8 to 2.0, preferably 0.9 to 1.7.

[0053] 4. The present invention provides a working electrode, which comprises the above-mentioned metal oxide-activated carbon composite material or the metal oxide-activated carbon composite material obtained by the above-mentioned preparation method.

[0054] 5. The present invention provides a method for preparing a working electrode, which comprises mixing a metal oxide-activated carbon composite material, a conductive agent, and a binder, and then coating the mixture on a current collector in the form of a slurry, pressing the mixture into an electrode sheet, and drying the sheet to obtain a working electrode.

[0055] Furthermore, in the above working electrode preparation method, the binder is one or more of polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), hydroxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and polyvinylidene fluoride (PVDF).

[0056] Furthermore, in the above working electrode preparation method, the conductive agent is one or more of conductive carbon black, acetylene black, graphene, carbon nanotubes, conductive graphite, and carbon fiber.

[0057] Furthermore, in the above working electrode preparation method, the current collector is one or more of nickel foam, aluminum foil, titanium foil, copper foil, and carbon paper.

[0058] Furthermore, in the above working electrode preparation method, the usage ratio of the composite material, the conductive carbon black and the binder is 7-9:0.5-2:0.5-2.

[0059] Furthermore, in the above working electrode preparation method, the pressure of pressing the electrode sheet is 5 to 15 MPa.

[0060] Furthermore, in the above working electrode preparation method, the drying temperature of the electrode sheet is 40-100°C.

[0061] Compared with the prior art, the metal oxide-activated carbon composite material and the preparation method thereof of the present invention have the following beneficial effects:

[0062] (1) In the metal oxide-activated carbon composite material of the present invention, not only can the metal oxide ensure the specific capacitance value of the composite material, but also the skeleton support of the carbon material can well alleviate the structural collapse of the metal oxide during the charge and discharge process, thereby ensuring the transfer of electrons. In addition, petroleum coke, which is widely available and inexpensive, is used as the raw material of the carbon material in the composite material, which has a significant advantage in raw material cost compared with carbon materials such as carbon aerogel, graphene, and carbon nanotubes.

[0063] (2) In the preparation method of the metal oxide-activated carbon composite material of the present invention, petroleum coke-based activated carbon is used as a skeleton support, and the composite process of the metal oxide and the carbon material is carried out simultaneously with the activation process of the petroleum coke, thereby achieving uniform dispersion of the metal oxide on the inner and outer surfaces of the activated carbon, achieving the structural stability of the active components of the composite material, and thereby increasing its long-term stability during electrochemical testing.

[0064] (3) The metal oxide-activated carbon composite material prepared by the present invention fully utilizes the characteristics of large specific surface area of ​​petroleum coke-based activated carbon and layered graphite microcrystals that are conducive to electronic conduction. At the same time, the highly dispersed nanoscale first metal oxide can contribute to a higher specific capacitance value. At the same time, the high dispersion of the first metal oxide on the surface of the activated carbon is conducive to reducing the resistance value of the composite material, thereby solving the problem of high resistivity when the first metal oxide is used as an electrode material.

[0065] (4) In the preparation method of the metal oxide-activated carbon composite material prepared by the present invention, the introduction of the auxiliary metal can not only prevent the accumulation of the first metal species during the activation process and play a better dispersion role, but also quickly convert the O2 in the oxidizing atmosphere into active oxygen during the post-oxidation treatment process, increase the concentration of active oxygen species through the generation and migration of oxygen vacancies, and selectively achieve low-temperature oxidation of the first metal, laying a foundation for the good electrochemical properties of the metal oxide-activated carbon composite material. DETAILED DESCRIPTION

[0066] The present invention will be further described below in conjunction with specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.

[0067] Unless explicitly stated otherwise, throughout the specification and claims, the term “comprise” or variations such as “include” or “comprising”, etc., will be understood to include the stated elements or components but not to exclude other elements or components.

[0068] Herein, for convenience of description, spatially relative terms, such as “below,” “beneath,” “lower,” “above,” “over,” “upper,” etc., may be used to describe the relationship between one element or feature and another element or feature.

[0069] In this document, the terms "first", "second", etc. are used to distinguish two different elements or parts, and are not used to limit a specific position or relative relationship. In other words, in some embodiments, the terms "first", "second", etc. can also be interchangeable.

[0070]

[0043] All numerical values ​​for parameters (eg, amounts or conditions) herein are to be understood as being modified in all instances by the term "about", whether or not "about" actually appears before the numerical value.

[0071] In the present invention, the specific surface area is obtained by nitrogen adsorption-desorption curve on Micromeritics ASAP 2020 adsorption instrument, the operating temperature is -196°C (liquid nitrogen temperature), the sample is pre-treated by dehydration at 300°C under nitrogen protection before testing, and the specific surface area is calculated by BET method.

[0072] The degree of defect refers to the Raman analysis of the wave number at 1590 cm -1 The absorption peak and wave number are at 1340 cm -1 The ratio of the peak heights of the absorption peaks.

[0073] The properties of the petroleum coke raw material used in the examples and comparative examples of the present invention are as follows: the sulfur content is 4.15 wt %, the volatile matter is 15.79 wt %, and the ash content is 0.79 wt %.

[0074] Example 1

[0075] Weigh 1.2 g of manganese acetate (Mn(CH3COO)2▪4H2O), 0.4 g of cerium nitrate (Ce(NO3)3▪6H2O), and 1.6 g of citric acid (C6H8O7▪4H2O), add to 30 mL of deionized water, stir until completely dissolved, and heat in a 70°C warm water bath until the solution becomes a sol; then place the sol in a vacuum drying oven at 80°C and dehydrate for 12 hours. The sol swells and dehydrates to transform into a dry gel. After cooling to room temperature, grind the dry gel into powder.

[0076] Weigh 1.2 g of petroleum coke and grind it into powder. Add the petroleum coke into 20 mL of 5 mol / L nitric acid solution, heat to 60 °C for reflux reaction for 4 h, then wash with deionized water until neutral, and dry at 105 °C for 6 h to obtain oxidized petroleum coke.

[0077] Weigh 3.6g potassium hydroxide, mix and stir with the obtained dry gel powder and oxidized petroleum coke powder, and put them into an activation furnace for heat treatment. First, replace the air in the activation furnace with a 500mL / min nitrogen gas flow at room temperature for 20min, heat it to 800℃ at 6℃ / min in a 200mL / min nitrogen atmosphere, and heat it at a constant temperature for 40min. Cool it down to 200℃ in a nitrogen atmosphere, switch the nitrogen to an oxygen-nitrogen mixed gas with an oxygen content of 10%, and after constant temperature oxidation treatment for 40min, switch to a nitrogen atmosphere and cool it to room temperature, then wash it with water and dry it at 120℃ for 4h to obtain a manganese dioxide-activated carbon composite material. The composition of the composite material is 50.7wt% activated carbon, 36.0wt% manganese dioxide, and 13.3wt% cerium oxide; the specific surface area is 621m 2 / g; the degree of defect is 1.16.

[0078] Electrochemical performance test of composite materials:

[0079] The prepared manganese dioxide-activated carbon composite material is applied to supercapacitors. The preparation process of the working electrode is as follows: the composite material, conductive carbon black and binder PTFE are mixed in a mass ratio of 8:1:1, then ground into slurry and coated on nickel foam, pressed into sheets, and placed in a 60℃ blast drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and 1mol / L sodium sulfate aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 398F / g, and the specific capacitance retention rate after 2000 cycles is 95.3%.

[0080] Example 2

[0081] Weigh 4.8g of manganese nitrate (Mn(NO3)2▪4H2O), 0.6g of lanthanum nitrate (La(NO3)3▪6H2O), and 9.6g of citric acid (C6H8O7▪4H2O), add to 50mL of deionized water, stir until completely dissolved, adjust the pH to 7.5 with ammonia water while stirring continuously, place in a 70℃ warm water bath and heat until the solution becomes a sol; then place the sol in a 90℃ vacuum drying oven and dehydrate for 10h. The sol swells and dehydrates to transform into a dry gel. After cooling to room temperature, grind the dry gel into powder.

[0082] Weigh 2.0 g of petroleum coke and grind it into powder. Add the petroleum coke into 30 mL of 3 mol / L nitric acid solution, heat to 70 °C and reflux for 4 h, then wash with deionized water until neutral, and dry at 120 °C for 6 h to obtain oxidized petroleum coke.

[0083] Weigh 10.0g potassium hydroxide, mix and stir with the obtained dry gel powder and oxidized petroleum coke powder, and put them into an activation furnace for heat treatment. First, replace the air in the activation furnace with a 500mL / min nitrogen gas flow at room temperature for 20min, heat it to 750℃ at 6℃ / min in a 200mL / min nitrogen atmosphere, and heat it at a constant temperature for 50min. Cool it down to 150℃ in a nitrogen atmosphere, switch the nitrogen to air, and after a constant temperature oxidation treatment for 40min, switch to a nitrogen atmosphere and cool it down to room temperature, then wash it with water and dry it at 105℃ for 6h to obtain a manganese dioxide-activated carbon composite material. The composition of the composite material is 34.5wt% activated carbon, 57.7wt% manganese dioxide, and 7.8wt% lanthanum oxide; the specific surface area is 426m 2 / g; the degree of defect is 1.25.

[0084] Electrochemical performance test of composite materials:

[0085] The prepared manganese dioxide-activated carbon composite material is applied to supercapacitors. The preparation process of the working electrode is as follows: the composite material, conductive carbon black and binder PTFE are mixed in a mass ratio of 8:1:1, then ground into slurry and coated on nickel foam, pressed into sheets, and placed in a 60℃ blast drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and 1mol / L sodium sulfate aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 418F / g, and the specific capacitance retention rate after 2000 cycles is 88.6%.

[0086] Example 3

[0087] Weigh 0.38g manganese nitrate (Mn(NO3)2▪4H2O), 0.38g lanthanum acetate (La(CH3COO)3▪1.5H2O), and 1.14g citric acid (C6H8O7▪4H2O), add to 20mL deionized water, stir until completely dissolved, adjust the pH to 7.5 with ammonia water while stirring continuously, place in a 50℃ warm water bath and heat until the solution becomes a sol; then place the sol in a 100℃ vacuum drying oven and dehydrate for 6h. The sol swells and dehydrates to transform into a dry gel. After cooling to room temperature, grind the dry gel into powder.

[0088] Weigh 5.4 g of petroleum coke and grind it into powder. Add the petroleum coke into 30 mL of 3 mol / L nitric acid solution, heat to 70 °C and reflux for 4 h, then wash with deionized water until neutral, and dry at 120 °C for 6 h to obtain oxidized petroleum coke.

[0089] Weigh 5.4g potassium hydroxide, mix and stir with the obtained dry gel powder and oxidized petroleum coke powder, and put them into an activation furnace for heat treatment. First, replace the air in the activation furnace with a 500mL / min nitrogen gas flow at room temperature for 20min, heat it to 900℃ at 6℃ / min in a 200mL / min nitrogen atmosphere, and heat it at a constant temperature for 20min. Cool it down to 100℃ in a nitrogen atmosphere, switch the nitrogen to an oxygen-nitrogen mixed gas with an oxygen content of 15%, and after constant temperature oxidation treatment for 60min, switch to a nitrogen atmosphere and cool it to room temperature, then wash it with water and dry it at 90℃ for 8h to obtain a manganese dioxide-activated carbon composite material. The composition of the composite material is 89.3wt% activated carbon, 4.6wt% manganese dioxide, and 6.1wt% lanthanum oxide; the specific surface area is 2102m 2 / g; the degree of defect is 1.11.

[0090] Electrochemical performance test of composite materials:

[0091] The prepared manganese dioxide-activated carbon composite material is applied to supercapacitors. The preparation process of the working electrode is as follows: the composite material, conductive carbon black and binder PTFE are mixed in a mass ratio of 8:1:1, then ground into slurry and coated on nickel foam, pressed into sheets, and placed in a 60℃ blast drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and 1mol / L sodium sulfate aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 287F / g, and the specific capacitance retention rate after 2000 cycles is 96.7%.

[0092] Example 4

[0093] Weigh 1.38g of manganese acetate (Mn(CH3COO)2▪4H2O), 0.43g of cerium acetate (Ce(CH3COO)3▪1.5H2O), and 1.81g of citric acid (C6H8O7▪4H2O), add to 40mL of deionized water, stir until completely dissolved, adjust the pH to 7.5 with ammonia water while stirring continuously, place in a 70℃ warm water bath and heat until the solution becomes a sol; then place the sol in a vacuum drying oven at 80℃ and dehydrate for 8h. The sol swells and dehydrates to transform into a dry gel. After cooling to room temperature, grind the dry gel into powder.

[0094] Weigh 3.2 g of petroleum coke and grind it into powder. Add the petroleum coke into 100 mL of 2 mol / L nitric acid solution, heat to 80° C. and reflux for 5 h. Then wash with deionized water until neutral, and dry at 120° C. for 6 h to obtain oxidized petroleum coke.

[0095] Weigh 12.8g potassium hydroxide, mix and stir with the obtained dry gel powder and oxidized petroleum coke powder, and put them into an activation furnace for heat treatment. First, replace the air in the activation furnace with a 500mL / min nitrogen gas flow at room temperature for 20min, heat it to 700℃ at 6℃ / min under a 200mL / min nitrogen atmosphere, and heat it at a constant temperature for 100min. Cool it down to 120℃ in a nitrogen atmosphere, switch the nitrogen to an oxygen-nitrogen mixed gas with an oxygen content of 5%, and after constant temperature oxidation treatment for 100min, switch to a nitrogen atmosphere and cool it to room temperature, then wash it with water and dry it at 80℃ for 12h to obtain a manganese dioxide-activated carbon composite material. The composition of the composite material is 68.9wt% activated carbon, 21.1wt% manganese dioxide, and 10.0wt% cerium oxide; the specific surface area is 986m 2 / g; the degree of defect is 1.32.

[0096] Electrochemical performance test of composite materials:

[0097] The prepared manganese dioxide-activated carbon composite material is applied to supercapacitors. The preparation process of the working electrode is as follows: the composite material, conductive carbon black and binder PTFE are mixed in a mass ratio of 8:1:1, then ground into slurry and coated on nickel foam, pressed into sheets, and placed in a 60℃ blast drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and 1mol / L sodium sulfate aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 426F / g, and the specific capacitance retention rate after 2000 cycles is 96.8%.

[0098] Example 5

[0099] Weigh 1.46g of manganese acetate (Mn(CH3COO)2▪4H2O) and 1.95g of citric acid (C6H8O7▪4H2O), add to 40mL of deionized water, stir until completely dissolved, adjust the pH to 7.5 with aqueous ammonia under constant stirring, place in a 70℃ warm water bath and heat until the solution becomes a sol; then place the sol in a vacuum drying oven at 80℃ and dehydrate for 8h. The sol swells and dehydrates to transform into a dry gel. After cooling to room temperature, grind the dry gel into powder.

[0100] Weigh 3.6 g of petroleum coke and grind it into powder. Add the petroleum coke into 100 mL of 8 mol / L nitric acid solution, heat to 40° C. and reflux for 2 h. Then wash with deionized water until neutral, and dry at 120° C. for 6 h to obtain oxidized petroleum coke.

[0101] Weigh 10.8g potassium hydroxide, mix and stir with the obtained dry gel powder and oxidized petroleum coke powder, and put them into an activation furnace for heat treatment. First, replace the air in the activation furnace with a 500mL / min nitrogen gas flow at room temperature for 20min, heat it to 850℃ at 6℃ / min in a 200mL / min nitrogen atmosphere, and heat it at a constant temperature for 50min. Cool it down to 180℃ in a nitrogen atmosphere, switch the nitrogen to helium-oxygen (oxygen volume fraction 10%), and after constant temperature oxidation treatment for 60min, switch to a nitrogen atmosphere and cool it down to room temperature, then wash it with water and dry it at 110℃ for 5h to obtain a manganese dioxide-activated carbon composite material. The composition of the composite material is 77.7wt% activated carbon and 22.3wt% manganese dioxide; the specific surface area is 1072m 2 / g; the degree of defect is 1.28.

[0102] Electrochemical performance test of composite materials:

[0103] The prepared manganese dioxide-activated carbon composite material is applied to supercapacitors. The preparation process of the working electrode is as follows: the composite material, conductive carbon black and binder PTFE are mixed in a mass ratio of 8:1:1, then ground into a slurry and coated on the nickel foam, pressed into a sheet, and placed in a 60°C blast drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and a 1 mol / L sodium sulfate aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 317F / g, and the specific capacitance retention rate after 2000 cycles is 91.5%.

[0104] Example 6

[0105] Weigh 3.7g of nickel nitrate (Ni (NO3)2▪6H2O), 0.4g of cerium acetate (Ce(CH3COO)3▪1.5H2O), and 4.1g of citric acid (C6H8O7▪4H2O), add to 50mL of deionized water, stir until completely dissolved, adjust the pH to 7.5 with ammonia water while stirring continuously, place in a 70℃ warm water bath and heat until the solution becomes a sol; then place the sol in a vacuum drying oven at 80℃ and dehydrate for 12h. The sol swells and dehydrates to transform into a dry gel. After cooling to room temperature, grind the dry gel into powder.

[0106] Weigh 6.4 g of petroleum coke and grind it into powder. Add the petroleum coke into 100 mL of 6 mol / L nitric acid solution, heat to 80° C. and reflux for 2 h. Then wash with deionized water until neutral, and dry at 120° C. for 6 h to obtain oxidized petroleum coke.

[0107] Weigh 16.2g potassium hydroxide, mix and stir with the obtained dry gel powder and oxidized petroleum coke powder, and put them into an activation furnace for heat treatment. First, replace the air in the activation furnace with a 500mL / min nitrogen gas flow at room temperature for 20min, heat it to 850℃ at 6℃ / min in a 200mL / min nitrogen atmosphere, and heat it at a constant temperature for 50min. Cool it down to 30℃ in a nitrogen atmosphere, switch the nitrogen to helium-oxygen (oxygen volume fraction 5%), and after constant temperature oxidation treatment for 100min, switch to a nitrogen atmosphere and cool it down to room temperature, then wash it with water and dry it at 115℃ for 6h to obtain a nickel oxide-activated carbon composite material. The composition of the composite material is 73.1wt% activated carbon, 21.9wt% nickel oxide, and 5.0% cerium oxide; the specific surface area is 864m 2 / g; the degree of defect is 1.19.

[0108] Electrochemical performance test of composite materials:

[0109] The prepared nickel oxide-activated carbon composite material is applied to supercapacitors. The preparation process of the working electrode is as follows: the composite material, graphene and binder PVDF are mixed in a mass ratio of 8:1:1, then ground into a slurry and coated on the nickel foam, pressed into a sheet, and placed in a 60°C blast drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and a 2mol / L potassium hydroxide aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 239F / g, and the specific capacitance retention rate after 2000 cycles is 82.2%.

[0110] Example 7

[0111] Weigh 1.5g of cobalt nitrate (Co(NO3)2▪6H2O), 0.3g of cerium nitrate (Ce(NO3)3▪6H2O), and 1.1g of citric acid (C6H8O7▪4H2O), add to 30mL of deionized water, stir until completely dissolved, adjust the pH to 8.0 with ammonia water while stirring continuously, place in a 60℃ warm water bath and heat until the solution becomes a sol; then place the sol in a vacuum drying oven at 80℃ and dehydrate for 12h. The sol swells and dehydrates to transform into a dry gel. After cooling to room temperature, grind the dry gel into powder.

[0112] Weigh 7.5 g of petroleum coke and grind it into powder. Add the petroleum coke into 100 mL of 6 mol / L nitric acid solution, heat to 100 ° C and reflux for 1 hour, then wash with deionized water until neutral, and dry at 120 ° C for 6 hours to obtain oxidized petroleum coke.

[0113] Weigh 22.5g potassium hydroxide, mix and stir with the obtained dry gel powder and oxidized petroleum coke powder, and put them into an activation furnace for heat treatment. First, replace the air in the activation furnace with a 500mL / min nitrogen gas flow at room temperature for 20min, heat it to 850℃ at 6℃ / min in a 200mL / min nitrogen atmosphere, and heat it at a constant temperature for 50min. Cool it down to 20℃ in a nitrogen atmosphere, switch the nitrogen to helium-oxygen (oxygen volume fraction 8%), and after constant temperature oxidation treatment for 80min, switch to a nitrogen atmosphere and cool it down to room temperature, then wash it with water and dry it at 80℃ for 12h to obtain a manganese dioxide-activated carbon composite material. The composition of the composite material is 88.1wt% activated carbon, 9.1wt% cobalt oxide, and 2.8% cerium oxide; the specific surface area is 1362m 2 / g; the degree of defect is 1.18.

[0114] Electrochemical performance test of composite materials:

[0115] The prepared manganese dioxide-activated carbon composite material is applied to supercapacitors. The preparation process of the working electrode is as follows: the composite material, carbon nanotubes and binder PTFE are mixed in a mass ratio of 7:1.5:1.5, then ground into slurry and coated on nickel foam, pressed into sheets, and placed in a 60℃ blast drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and a 6mol / L potassium hydroxide aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 295F / g, and the specific capacitance retention rate after 2000 cycles is 88.1%.

[0116] Comparative Example 1

[0117] 3.6 g of petroleum coke and 10.8 g of potassium hydroxide were weighed, mixed and stirred into powder, and loaded into an activation furnace for heat treatment. First, the air in the activation furnace was replaced with a 500 mL / min nitrogen gas flow at room temperature for 20 min, and the temperature was raised to 850 ° C at 6 ° C / min in a 200 mL / min nitrogen atmosphere. The temperature was kept constant for 50 min, and the nitrogen atmosphere was lowered to room temperature. Then, the activated carbon material was washed with water and dried at 100 ° C for 9 h to obtain a petroleum coke-based activated carbon material with a specific surface area of ​​2436 m 2 / g; the degree of defect is 0.96.

[0118] The prepared petroleum coke-based activated carbon material is applied to supercapacitors. The preparation process of the working electrode is as follows: the petroleum coke-based activated carbon material, conductive carbon black and binder PTFE are mixed in a mass ratio of 8:1:1, then ground into slurry and coated on nickel foam, pressed into sheets, and placed in a 60°C blast drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and a 1 mol / L sodium sulfate aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 268F / g, and the specific capacitance retention rate after 2000 cycles is 98.4%.

[0119] Comparative Example 2

[0120] Weigh 1.87g manganese nitrate (Mn(NO3)2▪4H2O), 0.56g cerium acetate (Ce(CH3COO)3▪1.5H2O), and 2.18g citric acid (C6H8O7▪4H2O), add to 60mL deionized water, stir until completely dissolved, adjust the pH to 7.5 with ammonia water while stirring continuously, place in a 70℃ warm water bath and heat until the solution becomes a sol; then place the sol in a vacuum drying oven at 80℃ and dehydrate for 8h. The sol swells and dehydrates to transform into a dry gel. After cooling to room temperature, grind the dry gel into powder.

[0121] The mixture was loaded into an activation furnace for heat treatment. First, the air in the activation furnace was replaced with a 500 mL / min nitrogen gas flow at room temperature for 20 minutes. The temperature was raised to 700°C at 6°C / min in a 200 mL / min nitrogen atmosphere, and the mixture was heat treated at a constant temperature for 50 minutes. The mixture was cooled to 200°C in a nitrogen atmosphere, and the nitrogen was switched to helium-oxygen (oxygen volume fraction 8%). After the constant temperature oxidation treatment for 60 minutes, the mixture was switched to a nitrogen atmosphere and cooled to room temperature. The mixture was then washed with water and dried at 120°C for 4 hours to obtain nano manganese dioxide. The material composition was 67.8 wt% manganese dioxide and 32.2 wt% cerium oxide. The specific surface area was 108 m 2 / g.

[0122] The prepared nano manganese dioxide composite material is applied to supercapacitors. The preparation process of the working electrode is as follows: nano manganese dioxide, conductive carbon black and binder PTFE are mixed in a mass ratio of 8:1:1, then ground into slurry and coated on nickel foam, pressed into sheets, and placed in a 60°C blast drying oven for drying for 12 hours. The three-electrode method is used for testing, with the composite material as the working electrode, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and 1 mol / L sodium sulfate aqueous solution as the electrolyte. The specific capacitance and cycle stability are tested using an electrochemical workstation, and the measured specific capacitance value is 309F / g, and the specific capacitance retention rate after 2000 cycles is 60.5%.

Claims

1. A metal oxide-activated carbon composite material, the composite material comprising a first metal oxide, a co-metal oxide and activated carbon, the first metal being selected from one or more of Group VIIB and Group VIII metals; the co-metal being at least one of lanthanide elements; based on the weight of the composite material, the first metal oxide content is 4-60%, the co-metal oxide content is 0.9-40%, and the activated carbon content is 20-95%; the preparation method of the metal oxide-activated carbon composite material comprises the following steps: (1) preparing a dry glue containing a first metal and a co-metal; (2) oxidizing the petroleum coke to obtain oxidized petroleum coke; (3) mixing the dry glue containing the first metal and the auxiliary metal obtained in step (1), the oxidized petroleum coke obtained in step (2) and an activator, and after mixing evenly, heat treating the mixture in an inert atmosphere at a temperature of 700 to 1000° C.; (4) treating the material obtained by the heat treatment in step (3) under an oxidizing atmosphere, and further washing and drying the obtained solid product to obtain a metal oxide-activated carbon composite material; the oxidation treatment temperature is 20 to 200° C., and the oxidation treatment time is 20 to 240 min.

2. The metal oxide-activated carbon composite material according to claim 1, wherein: Based on the weight of the composite material, the content of the first metal oxide is 5-50%, the content of the auxiliary metal oxide is 1-30%, and the content of the activated carbon is 20-90%.

3. The metal oxide-activated carbon composite material according to claim 1, wherein: The activated carbon is petroleum coke based activated carbon.

4. The metal oxide-activated carbon composite material according to claim 1, wherein: The first metal is one or more of manganese, nickel and cobalt.

5. The metal oxide-activated carbon composite material according to claim 1, wherein: The first metal is manganese.

6. The metal oxide-activated carbon composite material according to claim 1, wherein: The promoter metal is lanthanum and / or cerium.

7. The metal oxide-activated carbon composite material according to claim 1, wherein: The specific surface area of ​​the composite material is 300 to 2500 m 2 / g.

8. The metal oxide-activated carbon composite material according to claim 1, wherein: The specific surface area of ​​the composite material is 500~1600m 2 / g.

9. The metal oxide-activated carbon composite material according to claim 1, wherein: The defect degree of the composite material is 0.8 to 2.0; the defect degree refers to the wave number at 1590cm in Raman analysis. -1 The absorption peak and wave number are at 1340cm -1 The ratio of the peak intensities of the absorption peaks.

10. The metal oxide-activated carbon composite material according to claim 1, wherein: The defect degree of the composite material is 0.9 to 1.7; the defect degree refers to the wave number at 1590cm in Raman analysis. -1 The absorption peak and wave number are at 1340cm -1 The ratio of the peak intensities of the absorption peaks.

11. A method for preparing the metal oxide-activated carbon composite material according to any one of claims 1 to 10, comprising the following steps: (1) preparing a dry glue containing a first metal and a co-metal; (2) oxidizing the petroleum coke to obtain oxidized petroleum coke; (3) mixing the dry glue containing the first metal and the auxiliary metal obtained in step (1), the oxidized petroleum coke obtained in step (2) and an activator, and after mixing evenly, heat treating the mixture in an inert atmosphere at a temperature of 700 to 1000° C.; (4) treating the material obtained by the heat treatment in step (3) under an oxidizing atmosphere, and further washing and drying the obtained solid product to obtain a metal oxide-activated carbon composite material; the oxidation treatment temperature is 20 to 200° C., and the oxidation treatment time is 20 to 240 min.

12. The method for preparing the metal oxide-activated carbon composite material according to claim 11, wherein: The preparation of the dry gel containing the first metal and the metal promoter in step (1) is carried out by a sol-gel method, and the process is as follows: the first metal precursor, the metal promoter precursor and the complexing agent are dissolved in a solvent, the temperature is increased to a sol state, and then the dry gel containing the first metal and the metal promoter is obtained after drying.

13. The method for preparing the metal oxide-activated carbon composite material according to claim 11, wherein: The first metal is selected from one or more of Group VIIB and Group VIII metals.

14. The method for preparing the metal oxide-activated carbon composite material according to claim 11 or 13, wherein: The first metal is selected from one or more of manganese, nickel and cobalt.

15. The method for preparing the metal oxide-activated carbon composite material according to claim 11 or 13, wherein: The first metal is manganese.

16. The method for preparing the metal oxide-activated carbon composite material according to claim 12, wherein: The first metal precursor is a salt containing a first metal.

17. The method for preparing the metal oxide-activated carbon composite material according to claim 12 or 16, wherein: The first metal precursor is one or more of nitrate, sulfate, acetate and chloride.

18. The method for preparing the metal oxide-activated carbon composite material according to claim 12 or 16, wherein: The first metal precursor is one or more of manganese nitrate, manganese chloride, manganese sulfate, manganese acetate, nickel nitrate, nickel chloride, nickel acetate, nickel sulfate, cobalt nitrate, cobalt chloride, cobalt acetate, and cobalt sulfate.

19. The method for preparing the metal oxide-activated carbon composite material according to claim 11, wherein: The auxiliary metal is at least one lanthanide element.

20. The method for preparing the metal oxide-activated carbon composite material according to claim 11 or 19, wherein: The promoter metal is lanthanum and / or cerium.

21. The method for preparing the metal oxide-activated carbon composite material according to claim 12, wherein: The co-metal precursor is a salt containing the co-metal.

22. The method for preparing the metal oxide-activated carbon composite material according to claim 12 or 21, wherein: The metal precursor is one or more of nitrate, sulfate, acetate and chloride.

23. The method for preparing the metal oxide-activated carbon composite material according to claim 12 or 21, wherein: The auxiliary metal precursor is one or more of cerium nitrate, cerium sulfate, cerium chloride, cerium acetate, lanthanum chloride, lanthanum nitrate, lanthanum sulfate, and lanthanum acetate.

24. The method for preparing the metal oxide-activated carbon composite material according to claim 12, wherein: The complexing agent is one or more of citric acid, maleic acid, oxalic acid, ammonium oxalate, ethanolamine, diethanolamine, triethanolamine, polyvinyl pyrrolidone, glucose and tartaric acid.

25. The method for preparing the metal oxide-activated carbon composite material according to claim 12, wherein: The solvent is one or more of water and low molecular alcohol solvents.

26. The method for preparing the metal oxide-activated carbon composite material according to claim 12 or 25, wherein: The solvent is one or more of water, ethanol, methanol, isopropanol and n-butanol.

27. The method for preparing the metal oxide-activated carbon composite material according to claim 12, wherein: The mass ratio of the first metal precursor to the auxiliary metal precursor is 10:1 to 1:

1.

28. The method for preparing the metal oxide-activated carbon composite material according to claim 12 or 27, wherein: The mass ratio of the first metal precursor to the auxiliary metal precursor is 8:1 to 2:

1.

29. The method for preparing the metal oxide-activated carbon composite material according to claim 12, wherein: The mass ratio of the first metal precursor to the complexing agent is 3:1 to 1:

2.

30. The method for preparing the metal oxide-activated carbon composite material according to claim 12 or 29, wherein: The mass ratio of the first metal precursor to the complexing agent is 2:1 to 1:

2.

31. The method for preparing the metal oxide-activated carbon composite material according to claim 12, wherein: The heating treatment temperature is 35-70°C.

32. The method for preparing the metal oxide-activated carbon composite material according to claim 12, wherein: The first metal precursor, the auxiliary metal precursor and the complexing agent are dissolved in a solvent, and then the pH value of the system is adjusted to 5.5-7.

5.

33. The method for preparing the metal oxide-activated carbon composite material according to claim 12, wherein: The drying temperature is 60-120°C.

34. The method for preparing the metal oxide-activated carbon composite material according to claim 12, wherein: The drying temperature is 80-100°C.

35. The method for preparing the metal oxide-activated carbon composite material according to claim 11, wherein: The oxidation process of petroleum coke in step (2) is as follows: the petroleum coke is ground and crushed, mixed with an oxidant solution, and then washed and dried to obtain oxidized petroleum coke.

36. The method for preparing the metal oxide-activated carbon composite material according to claim 35, wherein: The oxidant is one or more of nitric acid, hydrogen peroxide, potassium permanganate and potassium perchlorate, and the concentration of the oxidant is 2-10 mol / L.

37. The method for preparing the metal oxide-activated carbon composite material according to claim 36, wherein: The concentration of the oxidant is 3 to 8 mol / L.

38. The method for preparing the metal oxide-activated carbon composite material according to claim 11, wherein: The activator in step (3) is one or more of sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, potassium bicarbonate, sodium bicarbonate, calcium hydroxide, and magnesium hydroxide.

39. The method for preparing the metal oxide-activated carbon composite material according to claim 11, wherein: In step (3), the activator is one or more of sodium hydroxide, potassium hydroxide and potassium carbonate.

40. The method for preparing the metal oxide-activated carbon composite material according to claim 11, wherein: Before the heat treatment in step (3), the gas in the device is fully replaced with an inert atmosphere, wherein the inert atmosphere is one or more of nitrogen, helium, neon, and argon.

41. The method for preparing the metal oxide-activated carbon composite material according to claim 11, wherein: The heat treatment temperature of step (3) is 700-900°C.

42. The method for preparing the metal oxide-activated carbon composite material according to claim 11, wherein: In step (4), the oxidation treatment temperature is 20 to 150° C. and the oxidation treatment time is 30 to 180 min.

43. The method for preparing the metal oxide-activated carbon composite material according to claim 11, wherein: In step (4), the oxidizing atmosphere is one or more of air, oxygen, and an oxygen-carrier gas mixture; the carrier gas in the oxygen-carrier gas mixture is at least one of nitrogen and an inert gas, and the volume concentration of oxygen in the oxygen-carrier gas mixture is 2 to 30%.

44. The method for preparing the metal oxide-activated carbon composite material according to claim 11 or 43, wherein: In step (4), the oxidizing atmosphere is at least one of air and an oxygen-carrier gas mixture; the carrier gas in the oxygen-carrier gas mixture is at least one of nitrogen and an inert gas, and the volume concentration of oxygen in the oxygen-carrier gas mixture is 5 to 25%.

45. The method for preparing the metal oxide-activated carbon composite material according to claim 11, wherein: The drying temperature in step (4) is 20 to 120°C.

46. ​​The method for preparing the metal oxide-activated carbon composite material according to claim 11, wherein: The drying temperature in step (4) is 40 to 105°C.

47. A working electrode, comprising the metal oxide-activated carbon composite material according to any one of claims 1 to 10.

48. The method for preparing the working electrode according to claim 47, comprising mixing the metal oxide-activated carbon composite material, the conductive agent and the binder, coating the mixture on the current collector in the form of a slurry, pressing the mixture into an electrode sheet, and drying the mixture to obtain the working electrode.

49. The method for preparing a working electrode according to claim 48, wherein: The binder is one or more of polytetrafluoroethylene, polyvinyl alcohol, hydroxymethyl cellulose, styrene-butadiene rubber and polyvinylidene fluoride.

50. The method for preparing a working electrode according to claim 48, wherein: The conductive agent is one or more of conductive carbon black, acetylene black, graphene, carbon nanotubes, conductive graphite, and carbon fiber.

51. The method for preparing a working electrode according to claim 48, wherein: The current collector is one or more of nickel foam, aluminum foil, titanium foil, copper foil and carbon paper.

52. The method for preparing a working electrode according to claim 48, wherein: The usage ratio of the composite material, the conductive carbon black and the binder is 7-9:0.5-2:0.5-2.

53. The method for preparing a working electrode according to claim 48, wherein: The pressure of pressing the electrode sheet is 5 to 15 MPa.

54. The method for preparing a working electrode according to claim 48, wherein: The drying temperature of the electrode sheet is 40 to 100°C.

Citation Information

Patent Citations

  • Preparation method of carbon particle / manganese dioxide composite electrode material

    CN105405680A

  • Carbon aerogel / manganese dioxide combined electrode material with multi-level structure, and preparation method thereof

    CN105826088A

  • Preparation method of carbon-manganese dioxide composite material

    CN108217733A

  • Preparation method of carbon nanotube / manganese dioxide composite electrode

    CN109637839A

  • Electrode material for lithium ion super-capacitor and preparation method thereof

    CN102832047A